Interventions to assist health consumers to find reliable online health information: a comprehensive review. - Kenneth Lee; Kreshnik Hoti; Jeffery D Hughes; Lynne M Emmerton (PLoS ONE)
Background Health information on the Internet is ubiquitous, and its use by health consumers prevalent. Finding and understanding relevant online health information, and determining content reliability, pose real challenges for many health consumers. Purpose To identify the types of interventions that have been implemented to assist health consumers to find reliable online health information, and where possible, describe and compare the types of outcomes studied. Data sources PubMed, PsycINFO, CINAHL Plus and Cochrane Library databases; WorldCat and Scirus 'gray literature' search engines; and manual review of reference lists of selected publications. Study selection Publications were selected by firstly screening title, abstract, and then full text. Data extraction Seven publications met the inclusion criteria, and were summarized in a data extraction form. The form incorporated the PICOS (Population Intervention Comparators Outcomes and Study Design) Model. Two eligible gray literature papers were also reported. Data synthesis Relevant data from included studies were tabulated to enable descriptive comparison. A brief critique of each study was included in the tables. This review was unable to follow systematic review methods due to the paucity of research and humanistic interventions reported. Limitations While extensive, the gray literature search may have had limited reach in some countries. The paucity of research on this topic limits conclusions that may be drawn. Conclusions The few eligible studies predominantly adopted a didactic approach to assisting health consumers, whereby consumers were either taught how to find credible websites, or how to use the Internet. Common types of outcomes studied include knowledge and skills pertaining to Internet use and searching for reliable health information. These outcomes were predominantly self-assessed by participants. There is potential for further research to explore other avenues for assisting health consumers to find reliable online health information, and to assess outcomes via objective measures.